Dimensionally stable water-blown polyurethane foam extended with bio-based propylene glycol and modified with paper waste sludge. Issue 2 (3rd April 2017) - Kairytė, Agnė; Ivdre, Aiga; Vaitkus, Saulius
Abstract: Paper waste sludge (PWS) is the main and the greatest by-product in paper production process, and its elimination as well as destruction is a primary environmental problem. This research explores the feasibility of such wastes to be used in polyurethane foam composites. It is well known that using water as a sole blowing agent has major drawbacks such as long demould time, shrinkage, high diffusion rate of carbon dioxide and etc.; therefore, the bio-based propylene glycol (RPG) is used in order to solve such problems. The addition of 20 parts by weight (pbw) of RPG eliminates the primary shrinkage of the foam composites when PWS is used in the amount varying from 5% to 20%, and improves the dimensional stability at 70°C and 90% relative humidity conditions. The addition of titanate coupling agent modified PWS particles increases the compressive strength of the final composites from ∼26% to ∼53%, from ∼17% to ∼31% and from ∼3% to ∼23% for, respectively, 10 pbw, 15 pbw and 20 pbw RPG extended foam composites.